Shop in a Box / Brandon Dee Binol ... [et al.] - Binol, Brandon Dee; Rosli, Maryam; Ahmad, Nafisah; Nordin, Norshazwaney; Hamzah, Nurul Rakinah; Simpaimun, Wan (2015)
Entrepreneurship acts as the movers of the economy who involved in the business of products or services. However, the entrepreneur have absolute right to make decision of what product to be produce based on relevancy. Business might be given profit or gain losses but it depends on the entrepreneur to manage the business as well. Normally, entrepreneur starts their business because they want to get maximum profit as their main goal. We determined to state Shop in A Box that provides boxes to be rent as our main product. Before we made this decision, we already did various methods to identify the opportunity in the business field. Besides that, before we start the plan to open this business, we have observed the planning area. We believe our business will develop in the future because of the good potential that we can see from the earlier. Our company name is Shop in A Box which established as partner's company. The date of commencement for our business is on 1s t January 2016. We take a long period of time because we want to identify the best way how to conduct the business and to find the capital for this business. j£ We have decided to start the business at S22, 2nd Floor IMAGO Shopping Mall K K Times Square Phase 2 Kota Kinabalu Sabah. We choose this place because it is one of the latest mall additions to the Kota Kinabalu City Centre; right in the middle of Times Square. The mall opened in March 2015 and has quickly become the place to visit for shoppers. We would like to offer something affordable rather than branded items in the mall. Our target customer is all kind of people but more focus on people that do not have enough budgets to open their own business. We confident to run this business field where we can gain our business target. Our priority is to make sure our service will help people that have creativity and innovation of their products but do not have enough budget to commercial it. This kind of business has the opportunity to gain profit and contribute to the economic development of our country. The business potential of this industry is we can expand our business and open our branch at other place. In our business, we will put a priority on the quality of the services as well as the customer's satisfaction. The reason why we involve on this business is due to some factor. Firstly, the concept of our business is not very popular in this region, so we have fewer competitors. We also believe it will make high profit and less capital. Next, our business does no need regular maintenance and no need to hire more workers because the shop is only needs a cashier and a promoter. We only have to prepare different sizes of boxes to be rent to the customers. Moreover, the different sizes and colors of our boxes will attract buyers to come to our shop. Lastly, our customers will be sell their products ranging from women or men products, health care products, children products, home ware products, handicrafts and everything that they can sell. Therefore the accomplishment of the business depends on the proper management and the cooperation between employers and employees. We provide high quality of our service by ensure our boxes satisfy with customer's choices. The great disciplinary by both party is require in order to ensure the business mission is achieve. Nevertheless, every manager is required in running its responsibility to ensure the performance under the targets market line to attain business successfully. Our target market helps us in provide services where we are focusing at IMAGO Shopping Mall as our first step before expand our business. We use several methods to get important information from various resources. There arc through interview and observations about society demands The result helps us to do a marketing analysis about our market size, determining our main competitors, the sales forecast and the marketing strategies. A business may require an administration manager as an important role to ensure the proper management to the organization. The manager is responsible to manage the employers and employees' salary, bonus, Employee Provident Fund (EPF), Social Security Organization (SOCSO) and other benefits that being provided to the employees. Moreover, administration manager helps to ensure that all the resources are being used effective and efficiently to run the business. All partners have sacrificed time, money, energy, expertise and everything to ensure that this business plan done very well. With hope and pray, this business plan could bring us the path to achieve our goals.